Collaborative Governance in Fulfilling Child Protection Rights in North Central Timor District - Utapara, Ludvina Lodan; Fritantus, Yohanes; Minggu, Pionisius; Kefi, Herminus; Agustian, Dimas (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to describe the cross-sector collaboration process in fulfilling the protection rights of child victims of violence which includes face-to-face dialogue, building trust, commitment to the process, mutual understanding and the final results achieved. This study uses a qualitative method with a descriptive approach. Data were collected through interviews, observations and documentation with key informants from the P3A Service, and other informants, namely the Resort Police, Social Service, Education Service, Health Service, District Attorney's Office, Population and Civil Registration Service, Yabiku and paralegals. Data analysis techniques include data reduction, data presentation and drawing conclusions. This study is guided by five research indicators, namely face-to-face dialogue proven by case titles, building trust proven by the regent's decree and also the strategic plan of the P3A Service, commitment to the process proven by a clear flow of handling child violence cases, shared understanding proven by joint meetings, and temporary impacts proven by decreasing cases of child violence. The results of this study indicate that collaborative governance in resolving cases of child violence has obtained quite satisfactory results, but there are still obstacles that the community does not fully understand the importance of child protection. The recommendation from this study is to increase the capacity of human resources through periodic socialization to the community and encourage active community involvement as pioneers and reporters related to child violence.